LEITURA, “CÁRCERE” E ISOLAMENTO SOCIAL: UM ESTUDO NO CONTEXTO DA SOCIOEDUCAÇÃO NO ESTADO DO PARANÁ - LASCOSKI, SONIELI PEDROSO (2022)
The study presented in this dissertation sought to investigate the social reading that the State and society make of adolescents in the prison scenario, in the current conjuncture of Brazilian society, emphasizing the norms in the state of Paraná, amid a global pandemic event. The specific objectives of this research were: (i) to describe in what way the historical and current documents contemplate the adolescents who fulfill socio-educational measures, emphasizing mainly the Estatuto da Criança e do Adolescente (Statute of the Child and Adolescent) and the Sistema Nacional de Atendimento Socioeducativo (National System of Socio-Educational Attendance); (ii) to identify in what way the historical and current documents highlight the public policies and the conception of subject in the socio education of the state of Paraná; (iii) to discuss about the role of reading, in its social sense, in the proposed conjuncture. This is bibliographic and documental research, guided by the methodology of situation analysis (SOUZA, 2014). The guiding problem of this research is based on the following questions: How does society ponder and live the pandemic moment? How is the historical and current reading, in official documents, of adolescents who are in detention? What is the conception and the social reading of the official documents, during the pandemic period, regarding socio-education in the state of Paraná? Through this research, it was possible to demonstrate the absence of criticality in today's society, as well as its implications in politics and social welfare. The reading carried out through bibliographic and documentary research makes explicit the absence of effective public policies for the full protection and re-socialization of juvenile offenders, as well as evidences the prejudice rooted by society in the prison scenario.